2019
DOI: 10.5194/bg-16-3941-2019
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community composition and abundance after millennia of submarine permafrost warming

Abstract: Abstract. Warming of the Arctic led to an increase in permafrost temperatures by about 0.3 ∘C during the last decade. Permafrost warming is associated with increasing sediment water content, permeability, and diffusivity and could in the long term alter microbial community composition and abundance even before permafrost thaws. We studied the long-term effect (up to 2500 years) of submarine permafrost warming on microbial communities along an onshore–offshore transect on the Siberian Arctic Shelf displaying a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 111 publications
0
14
1
2
Order By: Relevance
“…Possibly, changes in MCC occurring after burial have blurred these signatures. It thus appears that the preservation of paleoenvironmental signatures in the MCC of this loess-paleosol sequence is weaker compared to findings from some permafrost, aquatic or subseafloor sediments [34][35][36] .…”
Section: Discussioncontrasting
confidence: 58%
“…Possibly, changes in MCC occurring after burial have blurred these signatures. It thus appears that the preservation of paleoenvironmental signatures in the MCC of this loess-paleosol sequence is weaker compared to findings from some permafrost, aquatic or subseafloor sediments [34][35][36] .…”
Section: Discussioncontrasting
confidence: 58%
“…Figure 3), yet comparable to pore water from Yedoma deposits on Buor Khaya, northeastern Siberia (median: 317 mg L −1 , max: 1371 mg L −1 ; Schirrmeister et al, 2017). In addition, Ewing et al (2015) (Mitzscherling et al, 2019), or for Samoylov Island, ranging from 57 to 288 mg L −1 (Liebner et al, 2008).…”
Section: Unitmentioning
confidence: 65%
“…In addition, Ewing et al (2015) reported high maximum DOC values in Alaskan Yedoma pore water (median: 618 mg L −1 , max: 1551 mg L −1 ). For comparison, other studies from northeastern Siberia reported much lower pore water DOC values such as for early to middle Weichselian sediments on the Cape Mamontov Klyk, ranging from 4 to 305 mg L −1 (Mitzscherling et al, 2019), or for Samoylov Island, ranging from 57 to 288 mg L −1 (Liebner et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Сообщества, характеризуемые присутствием архейных филумов Euryarchaeota, Bathyarchaeota, Thaumarchaeota, Asgardarchaeota, по преобладающим филумам оказались схожими с сообществами современных прибрежных [Mitzscherling et al, 2019] и морских отложений, связанных с метаногидратными пинго [Gründer et al, 2019;Treude et al, 2020]. Как и представители домена Bacteria (см.…”
Section: заключениеunclassified
“…Доминирующими группами домена Archaea в вечной мерзлоте в районе м. Мамонтов Клык (западная часть моря Лаптевых) возрастом около 2500 лет являются анаэробные метаногенные аммонийокисляющие и метанокисляющие археи [Mitzscherling et al, 2019]. В вечной мерзлоте бух.…”
unclassified